2013
DOI: 10.1007/s00394-013-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between urinary phytoestrogen excretion and components of the metabolic syndrome in NHANES

Abstract: Our study shows that an increasing excretion of lignans, especially enterolactone, might be associated with a decreased presence of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
(86 reference statements)
1
22
0
Order By: Relevance
“…Dietary phytoestrogens have also been suggested to play a beneficial role in obesity, metabolic syndrome and type 2 diabetes (Bhathena and Velasquez, ; Cederroth and Nef, ; Crespillo et al , ; Jungbauer and Medjakovic, ; Struja et al , ). The meta‐analysis by Fang et al () reported an improvement in glucose metabolism and a significant reduction in insulin levels and insulin resistance in menopausal women, by especially genistein.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary phytoestrogens have also been suggested to play a beneficial role in obesity, metabolic syndrome and type 2 diabetes (Bhathena and Velasquez, ; Cederroth and Nef, ; Crespillo et al , ; Jungbauer and Medjakovic, ; Struja et al , ). The meta‐analysis by Fang et al () reported an improvement in glucose metabolism and a significant reduction in insulin levels and insulin resistance in menopausal women, by especially genistein.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 5 years, additional observational studies looking at urinary enterolactone or enterodiol have been published using NHANES data, which is a nationally representative sample of the U.S. population. Studies evaluated different classifications of urinary enterolignans and populations . The results from NHANES studies support that urinary enterolactone and enterodiol are associated with more favorable cardiometabolic risk factors, including BMI, abdominal obesity, triglycerides, HDL cholesterol, blood pressure, and inflammation, and that associations appear stronger for enterolactone.…”
Section: Other Phytoestrogensmentioning
confidence: 86%
“…In the last 5 years, additional observational studies looking at urinary enterolactone or enterodiol have been published using NHANES data, which is a nationally representative sample of the U.S. population. Studies evaluated different classifications of urinary enterolignans and populations [119][120][121][122][123].…”
Section: Other Phytoestrogensmentioning
confidence: 99%
“…The results from these previous studies are consistent with those of the present study. This protective effect of enterolactone on cardiovascular disease may be partially attributable to the inverse associations of its high urinary concentrations with inflammation biomarkers (C-reactive protein and white blood cell counts), obesity, and metabolic syndrome in human studies [56][57][58]. Animal and in vitro studies have offered additional mechanistic basis for the reduced cardiovascular mortality associated with elevated levels of urinary enterolactone [59][60][61].…”
Section: Discussionmentioning
confidence: 99%